A Study of Mechanical Properties of Concrete with Silica Fumes & Glass Fiber - Sanjay Agarwal, MohitVerma, Nitin Sahni (International Journal of Advanced Science and Technology, 2020)
Present study examines the effect of fiber and silica fume on the properties of plane concrete at different proportions. The Silica fume in weight fraction of 5% and 10% and the glass fiber 0.5% and 1% were used in this study.Total 90 specimens of concrete were prepared of five different design mixes and tested for workability, flexural strength, tensile strength and compressive strength. Influence of silica fume and fiber on the mechanical properties of plane concrete has been observed compared with each other.It was observed that10% silica fume gives optimum value of compressive strength (39.08N/mm2). This strength increased 33%, from the previous value, maximum value of flexural strength 11.92 N/mm2 which is increased 47% using1% fiber and obtained highest value of split tensile strength 4.01N/mm2 increased by 57% using 1%fiber.The results of the experimental program showed the improvement in the mechanical properties of concrete.